Reduced Function of the Glutathione S-Transferase S1 Suppresses Behavioral Hyperexcitability in Drosophila Expressing Mutant Voltage-Gated Sodium Channels. Issue 4 (1st April 2020) - Chen, Hung-Lin; Kasuya, Junko; Lansdon, Patrick; Kaas, Garrett; Tang, Hanxi; Sodders, Maggie; Kitamoto, Toshihiro
Abstract: Voltage-gated sodium (Nav ) channels play a central role in the generation and propagation of action potentials in excitable cells such as neurons and muscles. To determine how the phenotypes of Nav -channel mutants are affected by other genes, we performed a forward genetic screen for dominant modifiers of the seizure-prone, gain-of-function Dr osophila melanogaster Nav -channel mutant, para Shu . Our analyses using chromosome deficiencies, gene-specific RNA interference, and single-gene mutants revealed that a null allele of glutathione S-transferase S1 ( GstS1 ) dominantly suppresses para Shu phenotypes. Reduced GstS1 function also suppressed phenotypes of other seizure-prone Nav -channel mutants, para GEFS+ and para bss . Notably, para Shu mutants expressed 50% less GstS1 than wild-type flies, further supporting the notion that para Shu and GstS1 interact functionally. Introduction of a loss-of-function GstS1 mutation into a para Shu background led to up- and down-regulation of various genes, with those encoding cytochrome P450 (CYP) enzymes most significantly over-represented in this group. Because GstS1 is a fly ortholog of mammalian hematopoietic prostaglandin D synthase, and in mammals CYPs are involved in the oxygenation of polyunsaturated fatty acids including prostaglandins, our results raise the intriguing possibility that bioactive lipids play a role in GstS1 -mediated suppression of para Shu phenotypes.